1995
DOI: 10.1056/nejm199502023320501
|View full text |Cite
|
Sign up to set email alerts
|

Decline in Semen Quality among Fertile Men in Paris during the Past 20 Years

Abstract: During the past 20 years, there has been a decline in the concentration and motility of sperm and in the percentage of morphologically normal spermatozoa in fertile men that is independent of the age of the men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
306
5
27

Year Published

1998
1998
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 987 publications
(360 citation statements)
references
References 21 publications
22
306
5
27
Order By: Relevance
“…[1][2][3][4][5][6][7][8] By contrast, other studies have shown no evidence of deteriorating semen quality. [9][10][11][12][13][14][15][16] Some studies concern infertile couples, while others analyse normal sperm parameters.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] By contrast, other studies have shown no evidence of deteriorating semen quality. [9][10][11][12][13][14][15][16] Some studies concern infertile couples, while others analyse normal sperm parameters.…”
Section: Introductionmentioning
confidence: 99%
“…This challenges the assertions of previously published reports indicating a decline in sperm counts over a similar period of time. [1][2][3][4][5] …”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] We have recently published data showing no decline in sperm counts in men who banked sperm prior to vasectomy from 1970 to 1994 from three United States sperm banks at different geographic locations. 6 Since MacLeod and Gold 7 is still cited most prominently in defining a ''normal'' sperm count, we compared our sperm count data from 374 men with proven fertility who banked sperm prior to vasectomy in Minnesota from 1971 to 1994 to MacLeod and Gold's data from 1951 to look at whether sperm count distributions have changed over the last 40 years.…”
Section: Commentmentioning
confidence: 99%
See 2 more Smart Citations